A Socioeconomic Disaggregation of the World Bank Human Capital Index - D'Souza, Ritika; Gatti, Roberta; Kraay, Aart (World Bank, Washington, DC, 2019)
This paper documents inequality in health and education outcomes by constructing an index of human capital disaggregated by quintiles of socioeconomic status (SES) for a sample 51 mostly low- and middle-income countries. The index measures the expected future human capital of children born today, following the methodology of the World Bank Human Capital Index that was launched in October 2018. Within-country disparities in human capital outcomes across SES quintiles are large, accounting for roughly one-third of the total variation. On average, human capital outcomes increase with income at roughly the same rate across socio-economic groups within countries as they do across countries.